Lion metaphors in Chinese and English - Wei , Lixia; Wong , Bee Eng; Lim, C. B. (Universiti Putra Malaysia Press, 2013)
This study intends to explore the cultural similarities and differences between the lion metaphors in Mandarin Chinese and British English. Most previous studies on animal metaphors focussed on the expressions with human beings as the target domain by collecting data either from questionnaires or dictionaries based on the Conceptual Metaphor Theory. This study, however, focusses on the expressions with non-humans as the target domains and is based on data collected from authoritative corpora. Three hundred and ninety-seven metaphorical expressions in Mandarin Chinese were identified from the Modern Chinese Corpus compiled by the Centre for Chinese Linguistics of Peking University (CCL Corpus) and 241 metaphorical expressions in British English were identified from the British National Corpus (BNC). After analysing the expressions from the perspective of the source domain and the target domain, the results show that first, the metaphorical expressions in Mandarin Chinese are mainly projected from the lion’s appearance to non-humans, but those in British English are mainly projected from the lion’s characteristics to non-humans. Second, the expressions are mainly mapped onto seven target domains in each language; four are the same. In addition, the dominant evaluation of the seven target domains in each language is mostly neutral. Third, ten conceptual metaphors were generalised from Mandarin Chinese and one from British English. All of these indicate the occurrence of cultural similarities as well as differences in the lion metaphors in the two languages.